Maternal Health Care Practices among Mothers of a Selected Slum in Dhaka City - Karim, Mohoshina; Farah, Shayela (Journal of Enam Medical College, 2015)
Background: Bangladesh is a small South Asian country which became independent in 1971 after a bloody war. Rapid urbanisation in Bangladesh (26% of the 147.1 million inhabitants live in urban areas) is fuelling a growth in urban poverty, particularly in the urban slums where the quality of life is extremely poor. The average population density in slums was reported in 2005 as 831 persons per acre or 205,415 people per square kilometre.1 Early commencement of antenatal care by pregnant women as well as regular visits has the potential to affect maternal and foetal outcome. Objective: To assess the status of ANC service used by the pregnant mothers and their socio-demographic characteristics. Materials and Methods: A community-based cross-sectional study was conducted at Moghbazar slum area in Dhaka district of Bangladesh, during January to June 2014. A total of 161 slum dwellers were enrolled in the study. Information regarding education, occupation, monthly family income, antenatal care was gathered using a pretested structured questionnnare and data were analysed. Results: The majority respondents had knowledge about antenatal care and of them 89 (55.2%) completed ?3 visits. Forty five (47.8%) pregnant women received ANC from government hospitals. Nearly 72% mothers received ANC service from doctors and 16.9% received from family welfare visitors (FWV). Half of mothers were satisfied with the overall care provided to them. About 86.2% mothers said that they had to wait for more than two hours for check-ups. More than 50% received information about exercise and 36% were reassured about discussing fear and anxiety about pregnancy. Conclusion: This study reveals that antenatal care provided was not up to the mark of standard care and measures should be taken to improve it. J Enam Med Col 2015; 5(3): 166-169